The journal of critical care medicine (Universitatea de Medicină și Farmacie Tîrgu-Mureș, 2015)
The Journal of Critical Care Medicine is an international journal dedicated to publishing high-quality peer-reviewed articles about critical care medicine. The prominent themes covered by the journal include pathologies related to critical care patients, within a broad spectrum of disciplines and therapeutic areas, including, but not restricted to general surgery, perioperative care, cardiology, internal medicine, pneumology, infectious diseases, organ transplantation, emergency medicine, and neurology.